The Use of Prophylactic Antibiotics on Orthopaedic Procedures in an Academic Hospital in Indonesia - Setiawati, Yuani; Farhadi, Azmi (UNUSA Press, 2021)
Background: Surgical site infections (SSIs) are common surgical complications that will increase cost of treatment. The incidence of SSI can be prevented with antibiotic prophylactic. Uncompliance using of prophylactic antibiotics is one of the factors leading to the occurrence a microbes resistance. The data on the using of prophylactic antibiotics in Indonesia is still limited. Objective: This study aims to analyze the using of prophylactic antibiotic guideline on orthopaedic surgery. Methods: The study was conducted retrospectively using data from medical records on patients who had clean and clean-contaminated orthopedic procedures from 2013 to 2016 in the standard operating room of Dr. Soetomo hospital Surabaya. We analyzed the use of prophylactic antibiotics in terms of antibiotic selection, timing of administration, and the compliance to the prophylactic antibiotic local guidelines on orthopaedic surgery. Results: Overall, patient data from 2013 to 2016 was 5246 patients. The compliance rate of prophylactic antibiotics from 2013 to 2016 was 48.3%. This level of compliance uses a selection of antibiotics, dose of administration, delivery mode, delivery time, and route of administration. Conclusion: The results of this study have shown that the prophylactic antibiotic compliance rate on orthophaedic procedures in Soetomo Hospital from 2013 to 2016 was 48,3%. Antibiotic resistance control program quite effective at increasing compliance with the use of the prophylaxis antibiotics.